2016
DOI: 10.1038/srep33540
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic and climatic impacts on the biota within the Red River Fault, evidence from phylogeography of Cycas dolichophylla (Cycadaceae)

Abstract: Dramatic crustal deformation and river incision in Southwest China induced by the Indo-Asian collision have long been argued to contribute to the complicated landscapes, heterogeneous environment and abundant biodiversity in this region. However, biological impacts in promoting intraspecific phylogeographical subdivision and divergence along the Red River Fault zone (RRF) remain poorly understood. To investigate the possible biological effects of tectonic movements and environment variations within the RRF, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 62 publications
1
34
2
Order By: Relevance
“…The divergence time of the two lineages based on cpDNA and SCNG sequences is about 1.790 and 0.311 Ma, respectively, corresponding to a period of glacial cycle during the Middle Pleistocene, which verifies recent divergence in the former research (Nagalingum et al, 2011). The divergence time from cpDNA and SCNG was inconsistent, which is caused by different evolutionary rates and migration modes between organelle (pollen migration) and nuclear markers (pollen migration and seed migration; seed migration is very little) (Wolfe et al, 1987;Zheng et al, 2016). The recent divergence between the two lineages indicated that the species in clade B colonized Hainan Island in the Middle Pleistocene when land bridges formed (Shi et al, 2006;Huang et al, 2013b).…”
Section: Divergence Time and Demographic Dynamicsmentioning
confidence: 80%
“…The divergence time of the two lineages based on cpDNA and SCNG sequences is about 1.790 and 0.311 Ma, respectively, corresponding to a period of glacial cycle during the Middle Pleistocene, which verifies recent divergence in the former research (Nagalingum et al, 2011). The divergence time from cpDNA and SCNG was inconsistent, which is caused by different evolutionary rates and migration modes between organelle (pollen migration) and nuclear markers (pollen migration and seed migration; seed migration is very little) (Wolfe et al, 1987;Zheng et al, 2016). The recent divergence between the two lineages indicated that the species in clade B colonized Hainan Island in the Middle Pleistocene when land bridges formed (Shi et al, 2006;Huang et al, 2013b).…”
Section: Divergence Time and Demographic Dynamicsmentioning
confidence: 80%
“…Based on Bayesian Skyline Plot, a scenario of population expansion was suggested for both C. revoluta and C. taitungensis (Chiang et al., ), which contrary to the contraction experience occurred on southeast Asia Cycas species (Feng, Zheng, & Gong, ; Feng, Liu, et al., ; Gong et al., ; Zheng et al., ). One possible reason for this contrast is the different evolutionary processes of both topography and species in history (Gong et al., ; Huang et al., ; Kizaki & Oshiro, ; Shaw & Huang, ).…”
Section: Genetics Diversity and Differentiationmentioning
confidence: 99%
“…Most cycads live in valleys or monsoon forests on low-altitude slopes of ridges and cliffs (Fragnière et al, 2015), where is characterized by warm and moist conditions. However, the glacial-interglacial cycles, accompanied by a strengthened Asian winter monsoon dominating over continental southeast Asia (Cook & Jones, 2012), restricted Cycas into scattered habitats and hindered gene flow between populations (Feng et al, 2014;Liu et al, 2015;Xie, Jian, & Liu, 2005;Zhan et al, 2011;Zheng et al, 2016). Consequently, small populations were gradually isolated, which profoundly influenced the current demography, genetic structure, and population size.…”
Section: Human Activitymentioning
confidence: 99%
See 2 more Smart Citations